TRADITIONAL IMAGERY IN UZBEK AND GERMAN POETRY: AESTHETIC PARALLELS AND PHILOSOPHICAL DEPTH (World Bulletin of Social Sciences, 2025)
This article explores the poetic essence and aesthetic system of traditional imagery in Uzbek and German literature through a comparative lens. Drawing upon the works of Ogahiy, Uvaysiy, Nodira, Matnazar Abdulhakim, Khosiyat Rustamova, Goethe, Schiller, Jan Wagner, and Nora Gomringer, the study examines the philosophical and spiritual dimensions of symbolism. It highlights the interplay between Eastern Sufi thought and Western humanist ideals, revealing how traditional symbols such as “moon,” “rain,” “flower,” and “light” evolve within new poetic contexts. The paper emphasizes the renewal of imagery through rhythm, sound, metaphor, and intertextuality, showing how both poetic traditions transform inherited forms into new aesthetic expressions. Ultimately, the study concludes that traditional imagery serves as a unifying aesthetic bridge between two distinct yet spiritually connected cultures
Keywords: Traditional imagery; poetic structure; artistic thinking